Robert L. Smith: Visionary Leader, Extraordinary Mentor, & Beloved Colleague. (October 2021) - Southern, Stephen; Bradley, Loretta
This remembrance of Dr. Robert L. Smith, 63rd President of the American Counseling Association, contains recollections, tributes, and anecdotes about the life career of a major contributor to the profession of counseling. Dr. Smith's roles as collaborator and mentor are evidenced in the words of students, colleagues, and leaders. He founded the International Association of Marriage and Family Counselors and served as Executive Director of the organization. Personal qualities enabled Dr. Smith to share his gifts with those he mentored. His influence in counselor education will continue through the lives of those who knew and loved him.